2009
DOI: 10.1093/qjmed/hcp174
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in systemic sclerosis is associated with better ascertainment of internal organ disease: a retrospective cohort study

Abstract: SummaryBackground: Systemic sclerosis (SSc) has high mortality and morbidity. Current management focuses on early detection and treatment of organ-based manifestations. Aim: To determine whether the ascertainment of major organ complications of SSc has changed over time and if this is associated with better survival. Design: Retrospective cohort analysis. Methods: A total of 520 SSc patients, 234 with disease onset between 1990 and 1993 (historical cohort) and 286 with disease onset between 2000 and 2003 (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 18 publications
(16 reference statements)
7
85
0
14
Order By: Relevance
“…Increased frequency of coronary artery calcification in SSc patients compared to controls has also recently been reported in a pilot study of smaller sample size (27), despite the similar or lower rate of CAD in SSc patients compared with controls demonstrated by some studies (13,15). Although myocardial insufficiency in SSc has been attributed to microvascular disease (28) and imbalanced hemostasis (29) in earlier studies, coronary atherosclerosis has been increasingly revealed by conventional coronary angiography in SSc patients (13,14), concomitant with the significantly improved survival of these patients over the past decades (30). Other macrovascular diseases, such as peripheral vascular disease, have also been frequently reported in SSc patients (31,32).…”
Section: Discussionmentioning
confidence: 89%
“…Increased frequency of coronary artery calcification in SSc patients compared to controls has also recently been reported in a pilot study of smaller sample size (27), despite the similar or lower rate of CAD in SSc patients compared with controls demonstrated by some studies (13,15). Although myocardial insufficiency in SSc has been attributed to microvascular disease (28) and imbalanced hemostasis (29) in earlier studies, coronary atherosclerosis has been increasingly revealed by conventional coronary angiography in SSc patients (13,14), concomitant with the significantly improved survival of these patients over the past decades (30). Other macrovascular diseases, such as peripheral vascular disease, have also been frequently reported in SSc patients (31,32).…”
Section: Discussionmentioning
confidence: 89%
“…Early management might prevent morbidity and might save lives. Introduction of organ screening early in associated diseases has been shown to be associated with reduced disease progression and better outcomes [14]. Most cases of severe RP are associated with CTDs.…”
Section: Associated Conditions In Srpmentioning
confidence: 99%
“…Показано, что при раннем назначении адекват ной терапии ИПЛ и ЛАГ может улучшиться прогноз заболевания, в связи с чем крайне важно уточнить вариант легочного поражения, имеющийся у кон кретного пациента до появления клинической симп томатики дыхательной недостаточности [12]. Учи тывая медленно прогрессирующее течение ИПЛ у большинства пациентов с ССД и частое развитие ЛАГ через годы от начала ССД, большое значение приобретают данные инструментальных и лабора торных методов обследования, позволяющих доста точно рано прогнозировать развитие того или иного варианта легочного поражения.…”
Section: динамика систолического давления в легочной артерии за 5 летunclassified